Population and Poverty Projections for Nicaragua 1995 - 2015 - Lykke E. Andersen (Institute for Advanced Development Studies (INESAD), 2003)
This paper makes detailed population and poverty projections that take into account expected demographic changes (in terms of fertility, mortality, migration, and education) as well as differentials in social mobility by household type. Such projections could be useful for a variety of purposes ranging from assessment of necessary social investments (education facilities, health facilities, pension systems, etc), projections of the size of the working age population who will demand jobs, targeting of poverty alleviation policies, projections of migration flows, to negotiations with external donors and creditors. – – Este documento presenta proyecciones detalladas de población y pobreza que consideren los cambios demográficos y económicos esperados (esto último en términos de fecundidad, mortalidad, migración, educación y crecimiento del PIB) y sus reflejos en la movilidad económica por tipo de hogar. Las proyecciones de este tipo podrían ser útiles por una variedad de razones: desde la previsión de inversiones sociales necesarias (facilidades en educación y salud, sistema de pensiones, etc), las proyecciones del tama\~no de la población en edad laboral en busca de empleo (por condición de pobreza y educación), la focalización de políticas de reducción de la pobreza, la proyección de flujos migratorios, hasta las negociaciones con donantes y acreedores externos.
Keywords: J11; J13; 330; Population projections; poverty projections; social mobility; Nicaragua